PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS CANVA PADA PEMBELAJARAN PJOK MATERI LOMPAT JAUH TINGKAT SMP - Muhammad Suhron Siregar; Sukendro, Sukendro; Ugi Nugraha; Boy Indrayana; Hendri Munar; Wawan Junresti Daya; Agus Parman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop and evaluate the effectiveness of a Canva-based instructional video model for teaching long jump in Physical Education (PJOK) at the junior high school level. The research employed a Research and Development (R&D) design using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects were 32 eighth-grade students at SMPN 5 Tanjung Jabung Timur. Data were collected through expert validation sheets, student response questionnaires, and pretest-posttest learning outcomes. The validation results from media and material experts showed a validity score of 91.3% (very valid). The effectiveness test using paired sample t-test indicated a significant improvement in student learning outcomes (t = 9.87; p < 0.001). The average pretest score was 62.4, while the posttest score increased to 83.7. These findings demonstrate that Canva-based instructional videos are valid, practical, and effective in improving students’ cognitive and psychomotor learning outcomes in long jump material. The integration of digital media in physical education enhances student engagement, motivation, and conceptual understanding. Therefore, Canva-based video media can serve as an innovative alternative learning resource in PJOK instruction at the secondary school level.